Addressing fluctuation in article choice by Japanese learners of L2 English through explicit instruction. Issue 2 (9th October 2018) - Snape, Neal; Umeda, Mari
Abstract : This study examines the role of explicit instruction in article meanings to L1-Japanese learners of L2-English. An instruction group (n = 21), a control group (n = 16) and a native English speaker group (n = 9) participated in this study. Participants were asked to rate the acceptability of [±definite] and [±specific] sentences on a scale of 1–4 (1 = unacceptable; 4 = acceptable) in relation to a context for pre- and three post-tests. A pre-test was administered to both groups before instruction began and three post-tests were given to both groups. The instruction group received seven, sixty-minute lessons across seven weeks on instruction in the concepts of definiteness and specificity. Post-test 1 was administered to all participants at the end of the instruction period; post-test 2 was given after a twelve-week summer break; post-test 3 was one year after instruction had ended. The findings show that the instruction group made some gains in consolidating their understanding of the concepts during the instruction period, but after one year little explicit knowledge was retained.